Bidirectional scheduling for Wi-Fi 6 (IEEE (802.11ax) networks - Dilmaç, Abdurrahman. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
In recent years, Wi-Fi, along with Broadband Wireless, has been at the center of wireless communication. End-users owning laptops, tablets, and mobile phones enjoyed connected mobility. This massive adaptation brought more bandwidth demands. Consecutive IEEE 802.11 standard amendments were developed to overcome these requirements. Since hitting the gigabit barrier in IEEE 802.11ac, the main focus has shifted to increasing e ciency and reducing power consumption. Motivated by this, the latest amendment, IEEE 802.11ax, aims to minimize channel contention among network devices due to the very nature of random access, especially in dense areas. In this respect, IEEE 802.11ax, or Wi-Fi 6, brings several improvements focusing on these demands for better user experience and environment protection. In this regard, it introduces Target Wake Time (TWT) to make certain nodes sleep a de nite amount of time to preserve power, Overlapping Basic Service Set Preamble Detection (OBSS/PD) to exploit co-existence better, and nally, Orthogonal Frequency Division Multiple Access (OFDMA) based scheduled access to abandon previously used random access mechanisms by replacing it with scheduled access that allows an Access Point (AP) to schedule and manage tra c by making use of resource level parallelism and multiple spatial streams. This thesis investigates proper scheduling mechanisms and develops novel scheduler that work downlink and uplink directions. Our scheduler ensures maximum throughput delay. We tested our scheduler on state-of-the-art NS-3 network simulator and doubled the performance, leading to better power saving and greener Wi-Fi. NOTE Keywords : Wireless communication, Information and communication technologies, Computer communication, Duplex communication, Electronic communication.
Keywords: Wireless communication systems.; IEEE 802.11 (Standard)